An update on direct immunofluorescence for diagnosing dermatitis herpetiformis - Dmochowski, Marian; Gornowicz-Porowska, Justyna; Bowszyc-Dmochowska, Monika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
This mini-review presents an update on the direct immunofluorescence (DIF) for diagnosing dermatitis herpetiformis. The DIF of uninvolved, perilesional skin is a crucial laboratory procedure in diagnosing dermatitis herpetiformis (DH). IgA deposits at the dermal-epidermal junction (DEJ) of perilesional skin with DIF can also be found in coeliac patients with inflammatory skin diseases different from DH. In certain patients presenting with the rash resembling DH, the deposition of exclusively C3 at DEJ can be found. The term “granular C3 dermatosis” was proposed to name such a rash. Recent data on DH suggest that perhaps the very concept of DH that we are universally accepting now is misleading and should be revised.